"In God we trust" and other factors influencing trial of labor versus Repeat cesarean section. (3rd July 2018) - Pomeranz, Meir; Arbib, Nissim; Haddif, Limor; Reissner, Hana; Romem, Yitzhak; Biron, Tal
Abstract: Purpose: To investigate factors influencing women's decisions to undergo trial of labor after cesarean (TOLAC) or elective repeat cesarean delivery (ERCD) based on the Multidimensional Health Locus of Control (MHLC), religious observance and family planning. Materials and methods: Cross-sectional study of candidates for TOLAC or ERCD at two hospitals in Israel. Eligible women completed a demographic questionnaire and Form C of the MHLC scale. Results: The study included 197 women. Those who chose TOLAC ( N  = 101) were more religiously observant, wanted more children and had higher Internal and Chance health locus of control. Women who chose ERCD ( N  = 96) were more likely to be secular and had a higher health locus of control influenced by Powerful Others, notably physicians. Women not influenced by others were more likely to choose TOLAC. Conclusions: A woman's choice of TOLAC or ERCD is influenced by her sense of control over her health, degree of religious observance and number of children desired. Healthcare providers can use this information to better understand, counsel and educate women regarding appropriate delivery decisions. Women who feel in control of their health, educated about delivery options and are less influenced by provider preference, might choose TOLAC; thus, reducing the rate of unnecessary ERCD.